Review of New Clinical Aspects of Cardiac Pathology in Patients with COVID-19 Infection - Alonderytė, Audrė; Navickas, Giedrius; Samalavičius, Robertas Stasys; Šerpytis, Pranas (Acta medica Lituanica, 2021)
Background: COVID-19 disease is a huge burden for society and healthcare specialists. As more information is gathered about this new disease, it becomes clear that it affects not only respiratory, but also cardiovascular system.Materials and Methods: The aim of this review is to analyse the information about myocardial injury caused by COVID-19 and overview treatment options for these patients in publications which were published in the last 5 years. The data for this overview were collected in the PubMed database. Full-text articles were used for analysis when their title, summary, or keywords matched the purpose of the review. Only publications published in English that appeared in the last 5 years were analysed. For the analysis 14 publications were selected and analysed.Conclusion: COVID-19 infection could mimic ST-elevation myocardial infarction and it is crucial to differentiate the main cause and choose the appropriate treatment. Cardiovascular complications are related with poorer prognosis and higher mortality. This should be thoroughly considered by the healthcare specialists in order to choose appropriate treatment strategy. Patients with acute coronary syndrome (ACS) due to plaque rupture should receive dual antiplatelet therapy and full-dose anticoagulation if it is not contraindicated. Therefore, priority should be given to the acute coronary syndrome given the low evidence of new antiviral treatment effectiveness. Number of agents which are under investigation for COVID-19 may have interactions with oral antiplatelet drugs. Selected patients could receive immunosuppressive treatment as well as extracorporeal membrane oxygenation as a bridge to recovery.
Keywords: coronavirus; acute coronary syndrome; myocardial infarction; treatment